2012
DOI: 10.1109/toh.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

A High Performance Tactile Feedback Display and Its Integration in Teleoperation

Abstract: This paper presents the development of a compact tactile display and its integration in teleoperation. The system's operation is based on the display of surface shape to an area of the fingertip through a 4 × 4 array of tactors moving perpendicularly to the skin surface. The tactors are spring loaded and are actuated remotely by dc motors through a flexible tendon transmission. This novel implementation of conventional actuation principles achieves a compact design with superior performance compared to devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 30 publications
0
31
0
3
Order By: Relevance
“…Al combinar una IH cinestésica y una táctil aumenta la fidelidad en la interacción con el sistema virtual/remoto y mejora la percepción de realismo en el usuario, lo que potencialmente incrementa el nivel de inmersión virtual/remota (García-Hernández et al, 2014) que se evidencia también en la disminución del error de orientación en tareas de palpación (Unige et al, 2008). La materialización de este hecho se ha realizado con facilidad con la combinación entre una interfaz cinestésica comercial y una interfaz táctil desarrollada para el dedo, con lo que han logrado resultados satisfactorios Sarakoglou et al, 2012;Pacchierotti et al, 2013). Existe otro tipo de combinación en donde por medios táctiles se logran efectos cinestésicos simulados y sin enlaces o referencia de suelo, por medio de la combinación de impulsos de fuerza-torque que aplicados en la piel de la mano, dan la sensación de manipulación de objetos (Kamuro et al, 2011;Amemiya et al, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Al combinar una IH cinestésica y una táctil aumenta la fidelidad en la interacción con el sistema virtual/remoto y mejora la percepción de realismo en el usuario, lo que potencialmente incrementa el nivel de inmersión virtual/remota (García-Hernández et al, 2014) que se evidencia también en la disminución del error de orientación en tareas de palpación (Unige et al, 2008). La materialización de este hecho se ha realizado con facilidad con la combinación entre una interfaz cinestésica comercial y una interfaz táctil desarrollada para el dedo, con lo que han logrado resultados satisfactorios Sarakoglou et al, 2012;Pacchierotti et al, 2013). Existe otro tipo de combinación en donde por medios táctiles se logran efectos cinestésicos simulados y sin enlaces o referencia de suelo, por medio de la combinación de impulsos de fuerza-torque que aplicados en la piel de la mano, dan la sensación de manipulación de objetos (Kamuro et al, 2011;Amemiya et al, 2010).…”
Section: Discussionunclassified
“…El otro caso particular para una IH táctil es la de combinarse con una IH cinestésica cuyo efector final se sitúa en un punto, para convertirla en una IH táctil multipunto ; el mismo principio se ha aplicado en combinación con una o dos interfaces cinestésicas comerciales enfocado a mejorar la estabilidad en un ambiente de teleoperación (Sarakoglou et al, 2012;Pacchierotti et al, 2013). Se han dado casos particulares de aplicación de una IH táctil.…”
Section: Tabla 4 Dispositivos Hápticos-táctiles Comercialesunclassified
“…The results of the present study can be viewed as the most demanding specifications for combined tactile-kinesthetic haptic-feedback systems, including those that display slip (e.g., [21], [22], [15], [16]), tactile pin array (e.g., [22], [23]), contact orientation (e.g., [24], [25], [26]), and contact location [27].…”
Section: Design Guidelines For Tactile Displaysmentioning
confidence: 99%
“…Cincotti et al (2007) has provided a survey of vibrotactile feedback for EEG-based Brain Computer Interfacing applications. Sarakoglou et al (2012) has shown improvement in performing teleoperation in presence of tactile and force feedback. King et al (2009) has shown that without feedback of tactile information robotic manipulation are performed with greater forces than the optimum requirement for grasping objects.…”
Section: Introductionmentioning
confidence: 99%